Birthweight for gestational age: standard growth charts for the Polish population of full-term infants (Journal of Medical Science, 2022)
Introduction. Birthweight is one of the most important factors determining neonatal well-being. From an epidemiological viewpoint, a neonatal reference chart provides a picture of the health status of a population. Global customized growth charts seem to be the most practical in multicultural settings, allowing adjustment for ethnicity. However, regional charts might be a valuable contribution to reliable growth assessment. Our study aims to establish a reference tool for growth assessment and visualize the local potential, by creating standard charts based on the data from the tertiary center with the highest number of deliveries per year in Poland. Material and Methods. We retrospectively analysed 31,353 records from the electronic database of singleton births from a five-year period from a tertiary hospital in Poznań, Poland. We excluded pre-term deliveries and high-risk pregnancies basing on well-known factors influencing fetal growth, bringing the number of records to 21,379. The data were processed separately by gender (girls n=10,312, 48.2% and boys n=11,067, 51.8%). Percentiles were calculated for each week of gestational age. Means and standard deviations were determined. Results. Standard growth charts (including 3rd, 10th, 25th, 50th, 75th, 90th and 97th percentiles) are presented. Descriptive data of population distribution are shown. Conclusions. In conclusion, obtaining standard growth charts for mature newborns has created the opportunity for a more actual and adequate assessment of the Polish neonatal population. It should allow for the implementation of new standards in future research on perinatal care.